Teknologi Microbubble Pada Kolam Ikan Koi Untuk Meningkatkan Kualitas Air di Desa Sokong Kabupaten Lombok Utara - Bagus Dwi Hari Setyono; Septiana Dwiyanti; Damai Diniariwisan; Yuliana Asri; Muhammad Junaidi; Muhammad Sumsanto; Thoy Batun Citra Rahmadani (Universitas Mataram, 2023)
Koi fish cultivation activities are beginning to be developed in Sokong village, this is due to increasingly high demand, so it must be taken to improve the quality of koi fish production, one of which is by improving water quality. The availability of dissolved oxygen is one of the water quality parameters which is an indicator of good and bad water quality. So, to maintain the quality of dissolved oxygen, technology is needed that can maintain and meet oxygen needs. This community service activity aims to provide information regarding the application of microbubble technology to maintain dissolved oxygen in water so that it can increase the productivity of koi fish cultivation in Sokong village, North Lombok Regency. This service activity consists of several stages including location surveys, socialization and discussions, making and assembling microbubbles and testing microbubbles. Microbubble is a technology that functions to increase oxygen transfer through small water bubbles. The type of microbubble applied is the venturi type because it has a simple mechanism and the tools used are easy to obtain. This activity received a very good response as evidenced by the enthusiasm of partners participating in all stages. The benefit of this service is not only providing information on microbubble technology, but the use of this technology can provide solutions for managing and monitoring koi fish cultivation media in Sokong Village, North Lombok Regency.